Long-term efficacy of an antitachycardia pacemaker and implantable defibrillator combination. - Bonnet CA; Fogoros RN; Elson JJ; Fiedler SB; Burkholder JA (Pacing & Clinical Electrophysiology, 1991)
Antitachycardia pacemakers and implantable cardioverter defibrillators (JCD) were implanted in 14 patients to control recurrent hemodynamically stable ventricular tachycardia (VT). All patients underwent extensive preimplant testing in the electrophysiology laboratory documenting that in each patient at least 50 episodes of VT could be reliably terminated by an external model of the antitachycardia pacemaker. The burst scanning mode of antitachycardia pacing was used in all patients. ICDs were implanted solely as a back up should acceleration of VT occur, and all had high nonprogrammable rate cutoffs (mean 191 ± 12 beats/min). During a mean follow-up of 25 ± 6 months, 6,029 episodes of VT were treated in the 14 patients. Only 103 ICD discharges were required (approximately one discharge per 60 episodes of VT). Ten of the 14 patients received discharges from their ICDs. No deaths have occurred. All devices remain active and in the automatic mode. Thus, an antitachycardia pacemaker and ICD combination can safely and effectively terminate VT in highly selected patients who are subjected to extensive preimplant testing. In such patients, the vast majority of episodes of VT can be terminated with antitachycardia pacing, and only rarely is a discharge required from the ICD.